Peningkatan Kemampuan Pemecahan Masalah Penjumlahan Dan Pengurangan Siswa Kelas II SD Menggunakan Math Puzzle Games - Futry Ayu Lestari, Futry; Iwan Kuswidi; Ahmad Syawal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the improvement of addition and subtraction problem solving abilities of grade II students of SDN 1 Lalonggasumeeto through Math Puzzle Games using a quasi-experimental method with a pretest and posttest control group design, the subjects in this study were grade II students of SDN 1 Lalonggasumeeto. The results showed that students' addition and subtraction mathematical problem solving abilities through Math Puzzle Games were higher than the group that was not given treatment.